OsNPR1 GENE EXPRESSION IN RESPONSE TO SALYSILIC ACID IN RICE - Yip, Chee Kin; Yee, Tan Kah; Nadarajah, Kalaivani (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
NPR1 gene plays an important role in the activation of systemic acquired resistance (SAR). This research was conducted to examine the expression profiles of OsNPR1 gene in four rice varieties: Pongsu Seribu, MR219, MRQ74 and CO39 in response to treatment with salicylic acid (SA). All four varieties vary in their level of resistance to fungal sheath blight disease while Pongsu Seribu showed the highest tolerance. SA treatment did not result in an increase in the level of expression in all varieties except for CO39 which is highly susceptible to blast disease and OsNPR1 expressed in untreated CO39 was lower than the other three varieties. The overall results of this study show that SA did not result in increased expression of OsNPR1 gene in all varieties. We therefore may conclude that exogenous SA does not induce NPR1 gene in rice due to the higher endogenous levels of SA in rice. In addition SAR in rice may be controlled by non SA mediated pathways or combinatorial pathways.